Correlation Properties of Noise Signals at the Outputs of Receiving Channels with a Single Resonant Circuit - Xuan Chinh Vu; I. N. Davydzenka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
When suppressing active noise interference, an important task is to determine the mutual correlation function and the power of noise signals at the outputs of receiving channels. The solution of this problem makes it possible to analyze the influence of non-identical frequency characteristics of receiving channels on the quality of compensation of active noise interference. The analysis was carried out for a model of the frequency characteristics of the receiving channels in the form of the frequency response of a single resonant circuit in a narrow-band approximation. It was assumed that the frequency response of one of the channels differs from the second channel by the central frequency and bandwidth. In the analysis, an approximate approximation of the frequency response of the detuned channel was used, assuming a slight detuning of the parameters of the resonant circuit. The input noise of the receiving channels was assumed to be white. The use of the obtained results is demonstrated in obtaining an expression for the potential effectiveness of a single-channel autocompensator.